Examining the Impact of Movements of the Commodity Price on the Value of the Baltic Dry Index during the COVID-19 Pandemic - Radivojevic, Nikola; Muhovic, Almir; Josimovic, Milica; Pimic, Miroslav (Asian Journal of Economics and Empirical Research, 2021)
The Baltic Dry Index (BDI) is one of the most well-known indices, as it is perceived as a leading indicator of economic activity. Reductions in the movement of people, commodities, and capital in the conditions of economic crises, such as the one in 2008 and 2009, as well as the current economic crisis generated by the COVID-19 pandemic, were affected by the reduction of economic activities. It is interesting to point out that the analysis of the basic trend of the BDI movements in the period before the economic crisis shows that the index fell to near record lows just before the derivatives and credit crisis hit stocks full force. This is a clear signal that the index can be used as a tool for stock market forecasting. The paper aims to examine whether the changes in these raw materials affect the changes in the value of BDI. For these purposes in the paper was use GMM and 2SLS estimator. The results show that different raw materials have a different impact on the value of the BDI, which indicates that based on individual movements value of raw materials which composes the BDI cannot forecast its movement.